Guest Editor’s Introduction: Distributed Leadership for Interconnected Worlds - Lambropoulos, Niki; Vivitsou, Marianna (Human Technology, 2011)
The technological advancements in the second half of the previous century generated the potential for participatory decision making in organizational and governmental institutions. Moreover, the digital networking environments on the Internet that enabled this type of decision making were accompanied by the emergence and establishment of on-line communities. Under this perspective, the range of communication mediated by ubiquitous computing allows problems, ideas, and suggestions of a specific nature to be considered when gathered into organizational and institutional virtual spaces. Within these spaces, the voices of individual customers, workers, organizational stakeholders, and/or citizens can be articulated and brought to bear on services, practices, and policies, as well as to join voices with salient others. Such naturally or intentionally formed communities and groups require roles within them to function.